Ascending aortic disease in a patient with Marfan Syndrome. Case report - Stefania Del Cisne Serrrano Olmedo; Edison Ricardo Espinoza Saquicela (Case Reports)
Acute thoracic aortic dissection is caused by a tear in the intimal lining of the aorta, and is a symptom of acute aortic syndrome. The dissection allows the blood to pass through the rupture and separates the tunica intima from the tunica media or the tunica adventitia, creating a false intravascular light. Early diagnosis directly affects the chances of survival, since it is a medical emergency that can lead to death, even with optimal treatment. The following report presents the case of a 26-year-old man with a history of Marfan syndrome, retrosternal lancinating pain[LM1] , nausea, vomiting, and medium effort dyspnea that evolved to orthopnea, perioral cyanosis, murmur of aortic insufficiency and mitral systolic murmur. Complementary studies (chest x-ray, electrocardiogram, angiography, tomography, and echocardiogram) were performed, obtaining a diagnosis of Stanford type A ascending aortic dissection. Surgical treatment was indicated to replace the aortic root using a composite prosthesis and Bentall and De Bono coronary reconstruction. During the procedure, right coronary button destructuration occurred, so it was necessary to perform a venous bypass with a left internal saphenous venous hemoduct. Weaning extracorporeal circulation was achieved and then low expenditure of refractory character (despite vasopressor support at maximum dose), refractory ventricular fibrillation and asystole were observed. The patient did not recover and died as a consequence of acute transoperative myocardial infarction. The treatment for ascending aortic dissection remains a therapeutic challenge. Timely diagnosis is directly related to life expectancy in patients who suffer from this condition, hence the importance of proper diagnosis and management.